Effectiveness of mindfulness-based cognitive therapy in patients with bipolar affective disorder: A case series - Suvarna Shirish Joshi; Mahendra Prakash Sharma; Shivarama Varambally (International Journal of Yoga, 2018)
The present investigation was undertaken to examine the effects of mindfulness-based cognitive therapy (MBCT) on interepisodic symptoms, emotional regulation, and quality of life in patients with bipolar affective disorder (BPAD) in remission. The sample for the study comprised a total of five patients with the diagnosis of BPAD in partial or complete remission. Each patient was screened to fit the inclusion and exclusion criteria and later assessed on the Beck Depressive Inventory I, Beck Anxiety Inventory, Difficulties in Emotion Regulation Scale, Acceptance and Action Questionnaire-II, and The World Health Organization Quality of Life Assessment-BREF. Following preassessments, patients underwent 8–10 weeks of MBCT. A single case design with pre- and post-intervention assessment was adopted to evaluate the changes. Improvement was observed in all five cases on the outcome variables. The details of the results are discussed in the context of the available literature. Implications, limitations, and ideas for future investigations are also discussed.